Pembentukan Kata Majemuk dengan Unsur Kata Tobu 飛ぶ dalam Bahasa Jepang: Compound Word Formation with the Element Tobu 飛ぶ in Japanese - Adrianis Adrianis; Dhian Asri (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This article discusses the formation of compound words with the base verb Tobu 飛ぶ in Japanese, as found in the children's story Migawari de shimaokuri ni sareta reijō, kiken chitai no doragon-tachi o tenazukeru (身代わりで島送りにされた令嬢、危険地帯のドラゴンたちを手懐ける / The Noble Lady Sent to the Island as a Substitute Tames the Dragons of the Dangerous Zone). The process of forming compound words with the root word Tobu 飛ぶ employs a descriptive qualitative method. Data collection uses the observational method with tapping and note-taking techniques. Analysis is then conducted using the translational identity method and the referential identity method. The presentation of analytical results uses the informal method. The research findings on compound words with the base word Tobu 飛ぶ in Japanese indicate the occurrence of a morphological process, namely the deletion process of the masu ます suffix in the word Tobimasu 飛びます. The formation of compound words with the base word Tobu 飛ぶ generally combines with Group I verbs (godan doushi) and Group II verbs (ichidan doushi).